2012
DOI: 10.1016/j.ajhg.2012.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Cowchock Syndrome Is Associated with a Mutation in Apoptosis-Inducing Factor

Abstract: Cowchock syndrome (CMTX4) is a slowly progressive X-linked recessive disorder with axonal neuropathy, deafness, and cognitive impairment. The disease locus was previously mapped to an 11 cM region at chromosome X: q24-q26. Exome sequencing of an affected individual from the originally described family identified a missense change c.1478A>T (p.Glu493Val) in AIFM1, the gene encoding apoptosis-inducing factor (AIF) mitochondrion-associated 1. The change is at a highly conserved residue and cosegregated with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 23 publications
6
124
0
1
Order By: Relevance
“…16 Over the last few years, many studies have shown the value of exome sequencing for gene discovery purposes in neurological disorders. [19][20][21][22][23] Next-generation sequencing technologies have also accelerated gene discovery in patients with dHMN, 9,24 CMT 25,26 or other inherited neuropathies. [27][28][29] More recently, the use of exome sequencing for diagnostic purposes in genetic disorders with a high degree of genetic heterogeneity such as CMT is being explored.…”
Section: Discussionmentioning
confidence: 99%
“…16 Over the last few years, many studies have shown the value of exome sequencing for gene discovery purposes in neurological disorders. [19][20][21][22][23] Next-generation sequencing technologies have also accelerated gene discovery in patients with dHMN, 9,24 CMT 25,26 or other inherited neuropathies. [27][28][29] More recently, the use of exome sequencing for diagnostic purposes in genetic disorders with a high degree of genetic heterogeneity such as CMT is being explored.…”
Section: Discussionmentioning
confidence: 99%
“…References for all genes are in Supplementary Table S1 of the review by Lubs et al, 3 except for SYP, ZNF711, AIFM1, ZMYM3, KDM6A and WDR45. [13][14][15][16][17][18] …”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…While full knockout of AIF or 312 CHCHD4 are embryonic lethal [40,115], distinct AIF point mutations induce an array of 313 human diseases ranging from severe X-linked mitochondrial encephalomyopathy, Cowchock 314 syndrome (X-linked Charcot-Marie-Tooth disease with axonal sensorimotor neuropathy, 315 deafness and cognitive impairment) to infantile motor neuron disease or auditory neuropathy 316 spectrum disorder [116][117][118][119]. The fact that at least one of these pathogenic AIF mutations 317 (G308E, which gives rise to a severe phenotype) reduces AIF binding to CHCHD4 [40], 318 underscores the physiological importance of the AIF-CHCHD4 interaction.…”
mentioning
confidence: 99%